(untitled) (Jurnal Bahasa, 2011)
This study explores how nurses communicate with unconscious or sedated patients in Intensive Care Units (ICUs). The study measured the time spent and the content of verbal communication used by nurses when caring for this group of patients. Twenty ICU nurses were recruited as study participants based on systematic random sampling. Verbal communication data were collected by recording, transcribing and timing the nurses’ verbal communication with patients. Demographic data were obtained through individual interviews and nurses’ personal records. Data were analysed using thematic and content analysis. In conclusion, the findings revealed the need to improve awareness and education of nurses regarding the importance of communication with unconscious or sedated patients to promote their physical, mental and psychological recovery. Keywords: patient language, communication disorder, communication disorder, nurse-patient communication, communication time spent